Patch tests and hand eczema: retrospective study in 173 patients and literature review - Nathalie Mie Suzuki; Mariana de Figueiredo Silva Hafner; Rosana Lazzarini; Ida Alzira Gomes Duarte; John Verrinder Veasey (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Hand eczema (HE) is a highly prevalent, recurrent, and multifactorial disease. It encompasses a group of eczematous diseases that affect the hands, etiologically classified into irritant contact dermatitis (ICD), allergic contact dermatitis (ACD) and atopic dermatitis (AD). Few epidemiological studies in Latin America have investigated the characteristics of patients with this condition and the origin of the disease. Objectives To analyze the profile of patients diagnosed with HE submitted to patch tests aiming to determine its etiology. Methods A retrospective descriptive study was carried out on epidemiological data and patch tests of patients with HE treated at a tertiary hospital in the city of São Paulo from January 2013 to December 2020. Results A total of 173 patients were studied, whose final diagnosis was 61.8% of ICD, 23.1% of ACD and 5.2% of AD, with diagnostic overlap in 42.8% of the cases. The main positive and relevant patch tests were: Kathon CG (42%), nickel sulfate (33%), and thiuram mix (18%). Study limitations The number of treated cases and socioeconomic profile was limited to a vulnerable population group. Conclusion HE is a diagnosis in which overlapping etiologies are frequent, with the main sensitizers identified in ACD being Kathon CG, nickel sulfate and thiuram mix.